Sentiment Analysis of Air Pollution on Social Media: Systematic Literature Review - Permana, Yandi Dwi; Gofur, Abdul; Budi, Indra; Santoso, Aris Budi; Putra, Prabu Kresna (Sistemasi: Jurnal Sistem Informasi, 2024)
The need for a healthy and pollution-free environment is the basis of the problem that this study examines. Social media has become an integral aspect of daily existence for the majority engaged in the digital realm. It enables individuals from various backgrounds to utilize these platforms to stay updated on the latest information, such as the current state of pollution in Jakarta. This research explores the attitudes of social media users regarding their perspectives on air pollution in Jakarta. The method used includes conducting a Systematic Literature Review of academic papers released from 2020 to 2023. The results of this research can unveil the types of social media platforms utilized, the quantity of datasets, the procedures for data collection, data preprocessing techniques, and the commonly employed methods in sentiment analysis studies concerning the subject of air pollution.